Defining Life and Regulating Reproductive Choice - Will, Jonathan F. (The Hastings Center report, 2018)
If you blinked you may have missed it. The Department of Health and Human Services published its strategic plan for the 2018–2022 fiscal years, which includes the statement that HHS accomplishes its mission through programs and initiatives that serve and protect “Americans at every stage of life, from conception.” Of note, the “from conception” language is new and, depending on the direction President Trump's administration plans to go, could have profound implications for the regulation of reproductive services ranging from abortion to in vitro fertilization (IVF).